Synchronous in Merdeka Belajar Based Education Management Quality (EMQ - Manurung, P; H Maulidiah, R; L P Sari, P; Marsidin, S; ., Rusdinal; Supiatman, L; S Rambe, M (KnE Social Sciences, 2023)
Educational accreditation qualifications in schools are the substantial part of education synchronous management. Synchronous management in the education unit can be based on the situation or condition of education at a certain period. This article aims to study of policy quality as the foundation of education in Indonesian’s policy quality by using the qualitative approach throught extensive literature, interviewing experts and personal experience. The situation or condition can be seen from the formation of policies and or the election of new leadership. 1) Merdeka Belajar is integrity and the result of policy, and there may be influence from the political elite as a means of fulfilling these situations and conditions. 2) In the management of basic, middle, upper and higher education units it is known as independent learning. 3) Freedom to learn is a reflection of the government in Era 4.0, which requires students to understand freedom as the actualization of human identity as a real human being, and not only freely expressing attitudes, thoughts, feelings and actions, but also free in accepting learning from all aspects of knowledge. 4) The actualization of Merdeka Belajarshould be based on student-centred learning, students as problem solvers, critical thingking, and decision maker. Keywords: Merdeka Belajar; EMQ; education management quality